The Influence of the Philosophy of Freedom on Accounting Graduates' Career Decisions - Hasan Ashari; Trinandari Prasetyo Nugrahanti; Nur Aisyah Kustiani (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2025)
This study analyzes the influence of the philosophy of freedom on accounting students' career decisions after graduation and work. The purpose of the study is to explore the concept of freedom in philosophy and its application in career choices. The research method used is a quantitative method by sending a survey through snowball sampling involving 409 accounting graduate professionals. The results of the study indicate that although personal freedom is important, many accounting graduates are forced to choose a career based on external factors such as a good work environment, good compensation, and other external factors, compared to interests and idealism when attending high school. This study provides theoretical contributions on freedom in the context of the accounting profession and practical implications for the development of accounting education curriculum that pays more attention to the ethical dimensions and freedom in career decision making.